Clinical aspects and presumed etiology of multisystem inflammatory syndrome in children (MIS-C): A review - Anusrita Kundu; Swagata Maji; Suchismita Kumar; Shreya Bhattacharya; Pallab Chakraborty; Joy Sarkar (Elsevier, 2022)
The COVID-19 outbreak sparked by SARS-CoV-2, begat significant rates of malady worldwide, where children with an abnormal post-COVID ailment called the Multisystem Inflammatory Syndrome (MIS-C), were reported by April 2020. Here we have reviewed the clinical characteristics of the pediatric patients and the prognosis currently being utilized. A vivid comparison of MIS-C with other clinical conditions has been done. We have addressed the probable etiology and fundamental machinery of the inflammatory reactions, which drive organ failure. The involvement of androgen receptors portrays the likelihood of asymptomatic illness in children below adolescence, contributing to the concept of antibody-dependent enhancement.